2009
DOI: 10.1080/17455030902725630
|View full text |Cite
|
Sign up to set email alerts
|

A study for sound wave scattering by corrugated ground with complex trench structures

Abstract: Several trench structures in corrugated ground are investigated for the possibility of mitigating gun blast noise by numerical simulations. The blast noise usually includes large explosive energy with nonlinearity in the near field and exhibits a very lowfrequency spectrum. In this study, the linearity approximation for the noise is taken because the nonlinearity of the wave reaching the scatterer is not serious for many proved guns and the low-frequency characteristic is concentrated. The structures are desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The rock mass parameters are used in theoretical analysis and calculation as shown in Table 2. In our study, using geotechnical analysis modeling software and some self-compiled preprocessing programs, a threedimensional model of the topographic contour of the Jianshan open-pit was established [45,46]. Affected by the difference of terrain, lithology, blasting distance, and maximum charge, the acceleration transmitted by the blast wave will change irregularly.…”
Section: Three-dimensional Dynamic Stabilitymentioning
confidence: 99%
“…The rock mass parameters are used in theoretical analysis and calculation as shown in Table 2. In our study, using geotechnical analysis modeling software and some self-compiled preprocessing programs, a threedimensional model of the topographic contour of the Jianshan open-pit was established [45,46]. Affected by the difference of terrain, lithology, blasting distance, and maximum charge, the acceleration transmitted by the blast wave will change irregularly.…”
Section: Three-dimensional Dynamic Stabilitymentioning
confidence: 99%
“…The best known are micro-perforated absorbers and liners for acoustic noise reduction in vehicles or airplanes or for optimal acoustics in conference or lecture halls [1,2]. For surfaces consisting of rectangular grooves, approximate effective impedance models [3] have been derived and as detailed in [4] roughness can be used to modify effective impedances to enhance the surface transport noise reduction [5,6] mechanism is the creation of surface waves by roughness near grazing incidence [7]: the energy reaching a receiver can then be reduced by transferring the incident sound energy into these surface waves [8].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The surface structure may be manipulated such that the resulting energy reaching the receiver can be reduced at certain frequencies and for a given source-receiver geometry by the transfer of incident sound energy into surface waves and diffraction modes. 5 Under certain circumstances it has been found that grating structures can be represented as having an effective impedance similar to that of a porous hard-backed layer. 3 In an air-filled medium having slit-like pores with widths smaller than the incident wavelength, viscous friction and thermal exchange at the internal surfaces contribute to the surface impedance.…”
mentioning
confidence: 99%